Factors that influence the utilisation of ototoxicity monitoring services for patients on treatment for drug-resistant tuberculosis - Nhokwara, Primrose Tinashe (Division of Communication Sciences and Disorders, 2015)
Multi-drug resistance is increasingly becoming a challenge to tuberculosis control programmes globally. Treatment of multi-drug resistance tuberculosis (MDR-TB) includes aminoglycoside antibiotics which are known to cause hearing loss. Ototoxicity monitoring services are often provided to patients undergoing treatment for MDR-TB for early detection of ototoxic hearing loss to facilitate alerting the patients and relevant medical staff about the presence and progression of any hearing loss. Previously, models of managing patients with MDR-TB required mandatory hospitalization for at least 6 months. This made it relatively easy to monitor the hearing status of patients during their stay in the hospital. However, with recent introduction of policy guidelines that support management of patients with MDR-TB on an outpatients basis, ototoxicity monitoring for these patients will need to be reorganized to align with the new policy guidelines. The extent of the uptake of these services when patients are accessing them as outpatients is however, unknown. This study therefore aimed to describe the patterns of utilisation and explore the barriers and factors that facilitate the use of ototoxicity monitoring services when provided on an outpatient basis in the Cape Town Metropolitan area, Western Cape, South Africa.